TINJAUAN YURIDIS PEMUNGUTAN PAJAK PENGHASILAN BAGI PENERIMA BONUS ATLET PROFESIONAL DI INDONESIA - Ade Yusuf Hidayat; Ujang Bahar; Agus Surachman (Magister Hukum Sekolah Pascasarjana Unida, 2020)
All Indonesian people who already have income have generally become taxpayers, where they are required to report and pay taxes on income received. Both employers, employees and even athletes must pay and report their taxes. The objectives of this study are: 1) To find and analyze the juridical review of income tax collection for bonus recipients of professional athletes in Indonesia, 2) To find out and analyze the obstacles in collecting income tax for recipient of professional athlete bonuses in Indonesia. The research method used in this study is a normative juridical study that takes a qualitative approach that looks at and analyzes the legal norms in existing legislation and sociological research as supplementary data as primary data. The results of this study are: 1) Juridical review of income tax collection for recipients of professional athlete bonuses in Indonesia, that the tax on bonuses given to professional athletes can be excluded from the collection of Income Tax Article 21 because it is borne by the government. However, when submitting an Annual Notification Letter (SPT), taxpayers must still report the income received from the bonus, 2) Obstacles in collecting income tax for recipients of professional athlete bonuses in Indonesia, namely: regulations for implementing laws that are often inconsistent with the law, lack of guidance on income taxation, incomplete database, weak law enforcement against taxpayers if they violate, lack or lack of public awareness.